Estudo do perfil demográfico e do risco tromboembólico associados à fibrilação atrial na atenção básica do sistema único de saúde brasileiro utilizando-se a tecnologia da telemedicina - Moraes, Eraldo Ribeiro Ferreira Leao de [UNIFESP] (2018)
Background: The worldwide prevalence of atrial fibrillation (AF) varies between 0.1% and 4.0% and has been increasing. Little is known about the prevalence, stroke risk assessment and treatment of AF in Brazil. Methods: Our objective was to estimate the general prevalence of AF in several regions of Brazil using recordings of longdistance electrocardiogram (ECG) transmission. Patients from 125 outpatient general practitioner units covered by the telemedicine service of the Federal University of São Paulo were included. Only one ECG was considered per patient. A scripted telephone interview was also performed. Using the Brazilian Institute of Geography and Statistics (IBGE) method, we analyzed the data to project the prevalence of AF in the Brazilian population and estimate it for the year 2025. Results: Based on 676,621 ECG exams from January 2009 through April 2016, the mean age (±SD) of patients was 51.4 (±19.1) years, with 57.5% being female. The 7year period prevalence of AF was 2.2% (n=14,968). Based on the IBGE method, the prevalence of AF countrywide was projected to be 1.5% in 2016 and 1.7% in 2025. In the subset of patients with AF who were interviewed (n=301), 91 (30.2%) were not receiving any type of treatment for rate or rhythm control. Overall, 136 (64.7%) of the patients were on acetylsalicylic acid alone, 39 (18.7%) were using oral anticoagulants (OACs), and 7 (3.3%) reported concomitant use of acetylsalicylic acid and an OAC. Among patients interviewed, 189 (62.8%) were at high risk for stroke; only 28 (14.8%) were regular OAC users. Conclusions: Our study highlights the importance of screening for AF in the primary care setting in Brazil and identifies important gaps in the treatment of AF in this population.